2018
DOI: 10.3991/ijet.v13i12.8864
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence the Adoption of Postgraduate Online Courses

Abstract: A research about factors that lead students to choose online courses, as well as the acceptance of these courses, can provide very relevant information for higher education institutions’ decision makers to amend these offers to students’ interests and needs. An investigation through questionnaire was developed involving students who attended online post-graduate courses. It was intended to know which factors affect students' decision to opt for postgraduate online courses. A model, based on the TAM (Technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…The second finding of this study reveals that gender differences do not influence the users' perceived effect of Hello English on their communicative competence, and also their intention to use Hello English mobile application. These findings also confirm the results from previous studies which found that female and male participants perceived the same usefulness of mobile learning and show similar acceptance and intention to use mobile technology [9], [25], [28]. Thus, it is evident that English language learning mobile application could be disseminated equally for students' regardless of their gender differences because they would accept the application in the same way.…”
Section: Discussionsupporting
confidence: 88%
“…The second finding of this study reveals that gender differences do not influence the users' perceived effect of Hello English on their communicative competence, and also their intention to use Hello English mobile application. These findings also confirm the results from previous studies which found that female and male participants perceived the same usefulness of mobile learning and show similar acceptance and intention to use mobile technology [9], [25], [28]. Thus, it is evident that English language learning mobile application could be disseminated equally for students' regardless of their gender differences because they would accept the application in the same way.…”
Section: Discussionsupporting
confidence: 88%
“…According to Lin, Chen, and Fang ( 2010 ), in the e-learning context, perceived usefulness (PU) is described as the degree to which users believe that e-learning can support them to achieve teaching and learning objectives. Previous studies showed that PU had the most significant influence on attitude (Martinho et al, 2018 ; Ritter, 2017 ; Tarhini et al, 2015 ; Teo, 2012 ; Wong, 2015 ; Zogheib et al, 2015 ). Furthermore, PU also had a significant impact on behavioural intention toward e-learning adoption (Abdullah et al, 2016 ; Martinho et al, 2018 ; Scherer et al, 2019 ; Wong, 2015 ).…”
Section: Theoretical Frameworkmentioning
confidence: 95%
“…Previous studies showed that PU had the most significant influence on attitude (Martinho et al, 2018 ; Ritter, 2017 ; Tarhini et al, 2015 ; Teo, 2012 ; Wong, 2015 ; Zogheib et al, 2015 ). Furthermore, PU also had a significant impact on behavioural intention toward e-learning adoption (Abdullah et al, 2016 ; Martinho et al, 2018 ; Scherer et al, 2019 ; Wong, 2015 ). Based on the prior studies, we proposed the following hypotheses.…”
Section: Theoretical Frameworkmentioning
confidence: 95%
“…However, many researchers have developed their own models based on the original models. They design their instruments by adapting the model to the specific technology that they are analyzing and, in many cases, they add new constructs to the models (Park et al 2019 ; Pham and Tran 2020 ) or propose new models (Martinho et al 2018 ). Furthermore, structural equation modeling depends on the variables that the researcher includes to analyze the variability.…”
Section: Introductionmentioning
confidence: 99%